2009
DOI: 10.1021/la900149v
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Factors Affecting Alignment of Self-Assembling Nanofibers Patterned by Sonication-Assisted Solution Embossing

Abstract: We recently reported simultaneous self-assembly, alignment, and patterning of peptide amphiphile (PA) nanofibers over large areas by a soft lithographic technique termed sonication-assisted solution embossing (SASE). The present work examines the effect of ultrasonication, channel width, and nanofiber persistence length λ on the degree of alignment of nanofibers patterned by SASE. Polarized transmission and reflection infrared spectroscopy are used to establish a figure of merit for comparing nanofiber alignme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…This fibrillar structure is similar to those reported by analogous peptide amphiphiles rich in alanines immediately after the acyl chain (C 16 A x -peptide) reported in literature. 16,21,22 Hydrogen bonding occurs between adjacent PAs and runs axially along the micelles. It is not clear at this point whether there is a twist in the beta-sheets or they run parallel to the central axis.…”
Section: Resultsmentioning
confidence: 99%
“…This fibrillar structure is similar to those reported by analogous peptide amphiphiles rich in alanines immediately after the acyl chain (C 16 A x -peptide) reported in literature. 16,21,22 Hydrogen bonding occurs between adjacent PAs and runs axially along the micelles. It is not clear at this point whether there is a twist in the beta-sheets or they run parallel to the central axis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous FTIR studies of peptide amphiphiles have shown that the hydrogen bonding of β-sheets tends to be aligned along the long axis of fibers but with some amount of twisting or disruptions in the β-sheets 32,33,43. These studies were carried out on PA nanofiber monolayers using polarization modulation-infrared reflection absorption spectroscopy (PM-IRRAS), an FTIR method in which electric waves normal to a conductive surface are enhanced while the electromagnetic field parallel to the surface is eliminated.…”
Section: Ftirmentioning
confidence: 99%
“…147 In all cases, lowering the pH past the second apparent pK a results in precipitation, with TEM showing large flat ribbons at lower pH where a gel is no longer present. IR spectroscopy demonstrates that the β-sheets were broken up with evidence of random coils appearing at low pH.…”
Section: Fmoc-dipeptidesmentioning
confidence: 91%